Mitral valve surgery in dogs - Tiago, João André Dias (2017)
Mitral regurgitation secondary to myxomatous mitral valve disease is the most frequent cause of heart failure in dogs. Current treatment for this condition involves chronic medical therapy, which can improve quality of life and increase survival time of affected dogs. Despite this, classical medical treatment only addresses the consequences of mitral regurgitation and cannot halt the development of chronic heart failure. In human medicine, mitral valve replacement and mitral valve repair are commonly performed for resolving mitral regurgitation. Both these surgical techniques have been proven to be durable and safe, and provide excellent outcome. Given that mitral valve surgery is a standard procedure in human medicine, it is somewhat surprising that its use in dogs has not been deeply studied. Mitral valve surgery is an area which has been progressing slowly in veterinary medicine, and there are few reports available regarding its use. Results observed in mitral valve replacement publications contrast with human reports, although there is no current understanding on the reasons why this difference occurs. Mitral valve repair outcome has been improving and one recent study has accomplished great results, although more studies are required in order to verify the feasibility of this technique in dogs. The aim of this review is to discuss the current knowledge regarding mitral valve surgery in dogs, focusing on both surgical techniques and anesthetic procedures.